The effect of daily co-trimoxazole prophylaxis on natural development of antibody-mediated immunity against P. falciparum malaria infection in HIV-exposed uninfected Malawian children. - Herbert Longwe; Kondwani C Jambo; Kamija S Phiri; Nyanyiwe Mbeye; Thandile Gondwe; Tom Hall; Kevin K A Tetteh; Chris Drakeley; Wilson L Mandala (PLoS ONE, 2015)
Co-trimoxazole prophylaxis, currently recommended in HIV-exposed, uninfected (HEU) children as protection against opportunistic infections, also has some anti-malarial efficacy. We determined whether daily co-trimoxazole prophylaxis affects the natural development of antibody-mediated immunity to blood-stage Plasmodium falciparum malaria infection.Using an enzyme-linked immunosorbent assay, we measured antibodies to 8 Plasmodium falciparum antigens (AMA-1, MSP-119, MSP-3, PfSE, EBA-175RII, GLURP R0, GLURP R2 and CSP) in serum samples from 33 HEU children and 31 HIV-unexposed, uninfected (HUU) children, collected at 6, 12 and 18 months of age.Compared to HIV-uninfected children, HEU children had significantly lower levels of specific IgG against AMA-1 at 6 months (p = 0.001), MSP-119 at 12 months (p = 0.041) and PfSE at 6 months (p = 0.038), 12 months (p = 0.0012) and 18 months (p = 0.0097). No differences in the IgG antibody responses against the rest of the antigens were observed between the two groups at all time points. The breadth of specificity of IgG response was reduced in HEU children compared to HUU children during the follow up period.Co-trimoxazole prophylaxis seems to reduce IgG antibody responses to P. falciparum blood stage antigens, which could be as a result of a reduction in exposure of those children under this regime. Although antibody responses were regarded as markers of exposure in this study, further studies are required to establish whether these responses are correlated in any way to clinical immunity to malaria.